Endgame for ETA : elusive peace in the Basque Country - Whitfield, Teresa (Oxford University Press, 2014)
The violent Basque separatist group ETA took shape in Franco's Spain, yet claimed the majority of its victims under democracy. For most Spaniards it became an aberration, a criminal and terrorist band whose persistence defied explanation. Others, mainly Basques (but only some Basques) understood ETA as the violent expression of a political conflict that remained the unfinished business of Spain's transition to democracy. Such differences hindered efforts to 'defeat' ETA's terrorism on the one hand and 'resolve the Basque conflict' on the other for more than three decades. Endgame for ETA offer.